Keragaan Industri Rumah Tangga Aneka Kerupuk Hasil Laut di Kecamatan Socah-Kabupaten Bangkalan - Sugiarti, Teti (Rekayasa, 2009)
The study aimed  to observe  the various  ojhousehold  Industry  in Sub Sea  Cucumber  Crackers Socah.  This  research  method  survey  wzth  interview  techniques.  Respondents  numbered   23 processor  chips. Primary  data and  secondary  data. Research  conducted, it can be concluded that 1) Profile  of the entrepreneur  is characterized  byproductive  age, low education  but has a business experience a relatively long time. 2) Profile oJ the industry indicates that although the technology and production  process  zs relatively simple but highly pro pective  business is viewed from  the s pport and ease of raw ma!erial market. 3) Processing_ and Blonyo eggplant crackers are financzally  profitable  and  provzde  added  value  to the famzly   of fi.shermen.  and  4) Most busznesses rely on processor chips as the main incomefamilies.  The contribution of these businesses contributed 50-90 percent  offamily  income. Processing should increase the proauction  qzpacity, quality and product  quality zn tenns ofl!ackaging and1icensing. 2) Keep the support offinanczal znstitutions  or the government  in an ejjort to strengthen  business development  and  capital. and3) should be reactivated with business groups for perpetrators of agro-industries.Keywords: Domestic Industry, marine Results